Marketing in customer technology environments : prospective customers and magical worlds - Sudharshan, Devanathan (Emerald Group Publishing Limited, 2020)
With the rise of virtual reality, augmented reality, the internet of things and more, customers are more engaged, more involved, and easier to reach than ever; while being inundated with increasing amounts of marketing material. This straightforward guide takes you through these new technologies and shows how to leverage them to reach new markets.